The Challenges of Language Learning of the Study-Abroad Students of English Language Department of Islamic Higher Education in Kalimantan - Umar Fauzan; Nadia Nadia (Indonesian Journal of EFL and Linguistics, 2019)
The purpose of this study is to uncover: 1) How foreign students believe in learning English at Islamic higher education in Kalimantan, 2) The experience of foreign students in learning English at Islamic higher education in Kalimantan, 3) The challenges of foreign students in learning English at Islamic higher education in Kalimantan. This qualitative phenomenological research was to disclose the phenomenon of the entry of foreign students to Kalimantan. The main participants of the study were foreign students and English lecturers of state Islamic institute of Samarinda, state Islamic institute of Palangkaraya, and state Islamic university of Antasari. Meanwhile, the secondary participants of the study were foreign students and English lecturers from the state Islamic institute of Pontianak. The instruments were interviews, documentation, and observation. Analysis of research data used a model from Miles and Huberman consisting of data collection, data reduction, data presentation, and drawing conclusions. There are three important findings of this study. Firstly, foreign students believe in learning English at Islamic higher education in Kalimantan. They declared that the curriculum is appropriate, carried out by a good process, facilitated by adequate learning facilities, and implemented by competent teachers with varied learning methods. They were also assured to get the extra benefit of not only learning English but also learning Islamic material. Secondly, regarding to the experience of foreign students, there are two main things as our conclusion, namely: language learning benefit and socio-cultural benefit. In the context of learning English, they learned English material and felt more confident in speaking English. Meanwhile, from the socio-cultural aspect, foreign students at Islamic higher education in Kalimantan enhance their life experiences by learning the social life of the Indonesian people which enrich their life experiences. Thirdly, the challenges they faced were independent living, increasing self-confidence, mastering learning material, improving English speaking skills, and adapting to the environment, such as: food, language, or culture.